Constitutive Serotonin Tone Modulates Molecular and Behavioral Response to Chronic Fluoxetine Treatment: A Study on Genetic Rat Model - Kesić, Maja; Mokrović, Gordana; Tvrdeić, Ante; Miše, Branko; Štefulj, Jasminka; Čičin-Šain, Lipa (Frontiers in Psychiatry, 2021)
Selective serotonin reuptake inhibitors (SSRIs) are the most commonly prescribed medications for the treatment of mood disorders. Yet, individual response to SSRIs is highly variable, with only a portion of patients showing the desired therapeutic effect. To better understand the molecular basis underlying individual variability in response to SSRIs, here we comparatively studied behavioral and molecular consequences of chronic treatment with fluoxetine, a widely used SSRI, in two sublines of rats with constitutionally different serotonin (5HT) homeostasis: the high-5HT and low-5HT sublines. Platelet 5HT levels, a recognized indicator of SSRI efficacy, were decreased by fluoxetine treatment in both 5HT-sublines. On the other hand, biologically active plasma 5HT levels were reduced only in high-5HT rats. The anxiolytic effect of fluoxetine was also evident only in high-5HT rats, as supported by spatio-temporal and ethological behavioral measures in the elevated plus maze (EPM) test and exploratory behavior measures in the open field (OF) test. None of the behavioral EPM or OF measures were significantly altered by fluoxetine treatment in low-5HT rats. Unexpectedly, 5HT levels in cerebral cortices tended to be reduced only in low-5HT rats. Moreover, the effects of fluoxetine on cortical expression levels of 5HT-related proteins were also present only in low-5HT rats, with serotonin transporter (5HTT) and serotonin receptor type 1a (Htr1a) being down-regulated, while serotonin receptor type 4 (Htr4) was up-regulated by fluoxetine treatment. The obtained results support a role of individual 5HT tone as an important influencing factor on the biological actions of SSRI antidepressants.